REVIEW ETNOAGRONOMI PERLADANGAN PANGAN DI INDONESIA - Rusdi Evizal (Universitas Lampung, 2020)
Traditional field crop systems are practiced in both shifting cultivation systems and settled cultivation system. Traditional upland cropping systems play an important role in the production and food security of farmers. Transformation of the settled cultivation systems and plantations from the system of collecting forest products and shifting cultivation in Indonesia is discussed in this review. Futhermore we discuss ethno-agronomy of several traditional staple crop including sago, sweet potato, yam, taro, foxtail millet, and Coix lacryma-jobi.Keywords: Coix lacryma-jobi, foxtail millet, sago, sweet potato, yam, taro, shifting cultivation